PENEGAKAN HUKUM TERHADAP EKSISTENSI BECAK BERMOTOR UMUM (BENTOR) BERDASARKAN UNDANG-UNDANG NOMOR 22 TAHUN 2009 TENTANG LALU LINTAS DAN ANGKUTAN JALAN - Meta Suryani; Anis Mashdurohatun (UNISSULA, 2016)
The influence of industrialization which is identical to the use of machines in various areas of life influences the development of transportation. Humans begin creating motorized transport such as motorcycles, cars, aircraft, fire Crete, ships and including motorized pedicab and other motor tricycles. The existing of motorized pedicab caused controversy in some areas, because of the problems of legal regulation of traffic and regulatory issues. The problem statements that will be discussed are how the existence of a common motorized pedicab (bentor) as one of land transportation in Indonesia today, and how law enforcement on the existence of a common motorized tricycles (bentor) pursuant to Act No. 22 of 2009? The results showed that: the existence of a common motorized pedicab as one of land transport is increased in all parts of Indonesia; Enforcement of the law against the existence of a common motorized pedicab can not be effective, although Bentor has been unlawful provisions of Law No. 22 of 2009 and other regulations. The law enforcement is more focus on the principle of expediency, so the police do the discretion of the bentor as common operational as public transport, by seeing the its expediency for middle class, especially in district and rural areas and as a form of cultural characteristics existing communal society Indonesia.